A Novel Intrabody Communication Transceiver for Biomedical Applications - Seyedi, Mir Hojjat; Lai, Daniel; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This monograph explores Intrabody communication (IBC) as a novel non-RF wireless data communication technique using the human body itself as the communication channel or transmission medium. In particular, the book investigates Intrabody Communication considering limb joint effects within the transmission frequency range 0.3-200 MHz. Based on in-vivo experiments which determine the effects of size, situations, and locations of joints on the IBC, the book proposes a new IBC circuit model explaining elbow joint effects. This model not only takes the limb joint effects of the body into account but also considers the influence of measurement equipment in higher frequency band thus predicting signal attenuation behavior over wider frequency ranges. Finally, this work proposes transmitter and receiver architectures for intrabody communication. A carrier-free scheme based on impulse radio for the IBC is implemented on a FPGA.
Introduction -- Literature Review -- Experimental Methodology -- Empirical Measurement -- Body Channel Modeling -- IBC System Design.
Keywords: Electronics; Biomedical engineering; Signal processing; Electronics and Microelectronics, Instrumentation; Biomedical Engineering and Bioengineering; Signal, Speech and Image Processing